Identifikasi Konsep Privasi pada Indekos Massa Banyak, Studi Kasus Indekos Mahasiswi di Banda Aceh - Rafika Annisa; Maysarah Bakri; Sarvina Fitri Rizky (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2023)
Abstract. The indekost are businesses that rent out rooms in a house for a certain period and with a set payment schedule. Boarding houses involve owners and tenants who have no family ties and occupy the same building or site. To support its role as a place to live, the need for privacy in boarding houses is very important. This is based on the assumption that, compared to other building functions, a dwelling has the highest level of privacy requirements. This study was conducted to take a closer look at the efforts of boarding houses to maintain privacy architecturally. The object of research is in the Darussalam and Batoh Regions which are educational areas that have many boarding houses around them. This study uses a qualitative descriptive methodology. Data were collected through observation. The result of the research shows that research objects with separate masses have good privacy qualities. Another important finding is the orientation of the building and the placement of openings affect the quality of privacy in buildings.